SEJARAH PERKEMBANGAN HUKUM LINGKUNGAN DI INDONESIA - Risfalman Risfalman (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2018)
World War has produced many negative effects. Environmental pollution is one of the negative effects of world war. Pollution in the world is increasingly alarming. On this basis, the United Nations conducted an environmental conference in June 1972 in Stockholm, Sweden. The Stockholm Conference is considered the highest peak of environmental awareness at the international level. The Stockholm Conference produced an environmental legal concept called suitanable development. The results of the Stockholm conference underwent follow-up and obliged the conference participant countries to ratify it. Indonesia fulfilled this obligation by establishing Law No. 4 of 1982 concerning the basic provisions of environmental management. The law has several important instruments in environmental protection, namely an analysis of environmental impacts and environmental quality standards. In 1997 the law was revised and underwent several additions to environmental protection instruments. The final revision of environmental law is Law No. 32 of 2009 concerning environmental protection and management. The latest law has more complex environmental protection instruments